2015
DOI: 10.3906/biy-1505-52
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of genes related to melatonin and oxidative stress in human renal proximal tubule cells treated with antibiotic amphotericin B and its modified forms

Abstract: It acts through membrane receptors (MT1 and MT2), nuclear receptors (ROR/RZR -retinoid orphan receptors/ retinoid Z receptors), and nonreceptor-mediated mechanisms (Slominski et al., 2012). Melatonin, through its antioxidant properties, protects against damage of cellular components including DNA, cytosolic proteins, and cell membrane lipids (Yürüker et al., 2015). Studies on the antioxidant properties of melatonin are most commonly associated with agents that induce free radicals in cells (Nazıroğlu et al., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…It is well known that the long-term application of some commercial antifungals, like amphotericin B, is limited due to the toxicity towards human kidney cells associated with generation of oxidative stress [71,72], as well as towards normal human dermal fibroblasts [73]. Therefore, an evaluation of novel antifungal agents for the potential to provoke oxidative stress in vivo and inflict the oxidative stress-mediated damages is of great importance for their further medical application.…”
Section: Oxidative Stress In Zebrafish Embryos Upon Exposure Tomentioning
confidence: 99%
“…It is well known that the long-term application of some commercial antifungals, like amphotericin B, is limited due to the toxicity towards human kidney cells associated with generation of oxidative stress [71,72], as well as towards normal human dermal fibroblasts [73]. Therefore, an evaluation of novel antifungal agents for the potential to provoke oxidative stress in vivo and inflict the oxidative stress-mediated damages is of great importance for their further medical application.…”
Section: Oxidative Stress In Zebrafish Embryos Upon Exposure Tomentioning
confidence: 99%
“…A previous study has shown that the increase expression of MTNR1B is likely to decrease the release of insulin and lead to increasing risk of T2D (Tuomi et al 2016). Another research has confirmed amphotericin B with copper (II) ions (AmB–Cu 2+ ) as a complex formed by AmB and is likely to cause upregulation of MTNR1B (Gola et al 2015). In this study, it is illustrated that AmB is related to the oxidative injuries of the kidneys but studies about the influence of AmB–Cu 2+ on renal cells are rare (Gola et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Another research has confirmed amphotericin B with copper (II) ions (AmB–Cu 2+ ) as a complex formed by AmB and is likely to cause upregulation of MTNR1B (Gola et al 2015). In this study, it is illustrated that AmB is related to the oxidative injuries of the kidneys but studies about the influence of AmB–Cu 2+ on renal cells are rare (Gola et al 2015). Our evidence does not suggest a straightforward relationship between MTNR1B and eGFRcrea and T2D, but may provide a new insight for studying the common mechanism of eGFRcrea and T2D in genetic aspect.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of the use of amphotericin B, however, is its high toxicity to human cells. One of the proposed mechanisms of the nephrotoxicity of amphotericin B is the induction of oxidative stress [11]. However, the mechanism of AmB toxicity has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we studied the influence of modified forms of AmB: the complex of AmB with copper(II) ions (AmB-Cu 2+ ) and the oxidized form of AmB (AmBox). The first of them is less toxic for RPTECs while maintaining its antifungal activity [11,12]. Oxidized forms of AmB may occur in the patient's circulation during therapy, causing the observed side effects [13].…”
Section: Introductionmentioning
confidence: 99%